Innovative construction materials: graphene-based smart composites - Salvatore Polverino; Renata Morbiducci; Antonio E. Del Rio Castillo; Francesco Bonaccorso (Tema, 2021)
Over the recent decades, the cement composites sector has been characterised by experimentation and production of the so-called intelligent concrete, that can adjust their characteristics by reacting to external stimuli. The ultimate evolution of the concrete performance has been achieved thanks to the use of multifunctional fillers, transforming a traditional concrete into a smart concrete. Graphene, a two-dimensional material, is opening new avenues for innovative applications in the construction sec-tor. This paper reports the first results of using pure crystalline few-layers graphene as an additive in cement composites.